Symmetric duality for lexicographic problems of linear programming - Eremin , I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A symmetric pair of lexicographic linear-programming (LP) problems, connected by regular relations, is formulated for problems of multicriteria linear optimization. A duality theorem for improper linear-programming problems (ILPP) is constructed in terms of lexicographic optimization.